2021
DOI: 10.1186/s13643-021-01695-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of prostate cancer presentation, etiology, and screening practices among women: a mixed-methods systematic review

Abstract: Background With the burden of prostate cancer, it has become imperative to exploit cost-effective ways to tackle this menace. Women have demonstrated their ability to recognize early cancer signs, and it is, therefore, relevant to include women in strategies to improve the early detection of prostate cancer. This systematic review seeks to gather evidence from studies that investigated women’s knowledge about (1) the signs and symptoms, (2) causes and risk factors, and (3) the screening modalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…With evidence of women playing a vital role in PCa control in our previous review study [ 13 ], the cost of diagnosis and management of the disease is essential for women to prioritize their family resources and how the country would allocate its national resources to control PCa. The evaluation of the COI of PCa, through an analysis of the direct health cost due to the unavailability of data, in Ghana is therefore essential.…”
Section: Introductionmentioning
confidence: 99%
“…With evidence of women playing a vital role in PCa control in our previous review study [ 13 ], the cost of diagnosis and management of the disease is essential for women to prioritize their family resources and how the country would allocate its national resources to control PCa. The evaluation of the COI of PCa, through an analysis of the direct health cost due to the unavailability of data, in Ghana is therefore essential.…”
Section: Introductionmentioning
confidence: 99%
“…This pilot study served as the third stage of the development of a robust Akan tool, with appropriate psychometric properties, aimed at studying prostate cancer awareness amongst Ghanaian women. The first stage of the tool development involved the conduct of a systematic review which brought together various questionnaire items [ 2 ]. The questionnaire items were then combined to develop an English version data extraction tool which was translated into the Akan language, certified, and subjected to validity and reliability assessments as part of the second stage of the tool development [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Rashid et al (2007), women reported poor prostate cancer knowledge and their inability to contribute to the timely detection of prostate cancer and stressed the need for education and inclusiveness [ 1 ]. Drawing on the evidence from a systematic review conducted by Wiafe and colleagues (2021), it has become relevant to investigate the knowledge, awareness and perception of prostate cancer (PCa) in African women [ 2 ]. According to the authors, none of the seven primary (7) studies that were included in their review was conducted in Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tey have also been proven to play a key role in making decisions in the treatment of their spouse or partner diagnosed with prostate cancer, as well as in screening. However, few studies have been conducted on women's knowledge of prostate cancer, and it is necessary to map the evidence to establish their knowledge as a public health tool to reduce the disease [37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%